Pengaruh Penggunaan Catalytic Converter Kuningan (Cu-Zn) Terhadap Konsentrasi Polutan Gas Buang Motor Bensin Empat Langkah - Andi Sanata, ; Djoko Sungkono, (Teknika, 2006)
One alternative for reduction pollutant is treating after combustion syatem. Placing catalytic converter in exhaust gas system, pollutant (CO and HC) can be decrease by chemical process such as oxidation and reduction.The experiment is being done at Internal Combustion Engine Laboratory Mechanical Engineering Department FTI-ITS. In this experiment Honda Karisma 125 cc motorcycle engine was used. The test result are comparing between standart engine experiment and engine experiment with catalytic converter on exhaust system.The analysis shows that brass (Cu-Zn) as catalytic converter with 160 gr catalyst mass treatment decreases CO pollutant up to 79,92% and HC pollutant up to 62,16% from standar engine treatment.